The Role of Ethnomathematical Context in Geometric Reasoning: A Van Hiele-Based Analysis of Indonesian Eighth-Graders - Wibawa, Fayza Sandya; Kania, Nia (Jurnal Pendidikan Progresif, 2025)
The Role of Ethnomathematical Context in Geometric Reasoning: A Van Hiele-Based Analysis of Indonesian Seventh-Graders. Objective: This study aims to analyze students' geometric thinking skills on plane geometry material based on Van Hiele's theory. An ethnomathematics approach was employed, focusing on the geometric patterns and shapes found in the ornaments, windows, and domes of local mosques, which serve as representations of plane geometry. This study is intended to describe the profile of students' thinking levels and the difficulties that arise at each stage of geometric thinking, without testing the improvement or influence of specific interventions. Methods: The study employed a qualitative descriptive approach with 22 eighth-grader students from a public junior high school in Majalengka Regency, Indonesia, as participants. The instruments used included a diagnostic test based on Van Hiele's theory and unstructured interviews to explore students' reasoning patterns. Data were analyzed using thematic analysis through the stages of reduction, presentation, and conclusion drawing, and validated through triangulation between test and interview results. Classification of thinking levels was carried out by matching students' answers and explanations to the indicators of each Van Hiele level. Findings: The study's results showed a significant decline in the achievement of each level of geometric thinking. All students reached the visualization stage; 81.8% reached the analysis stage, 22.7% reached informal deduction, and only 9.09% reached formal deduction, while no students reached the rigor stage. The sharp decline from the analysis to the deduction stage indicates students' limited ability to connect the properties of shapes and reason logistically. Interviews revealed that the local cultural context facilitated the visualization of shapes, but did not fully encourage higher deductive abilities. Conclusion: Students’ geometric thinking skills are primarily at the stages of visualization and analysis. The use of ethnomathematical contexts has the potential to act as an early cognitive bridge, facilitating students’ recognition of shapes and their properties. Compared to standard geometry problems, ethnomathematical problems better facilitate initial conceptual understanding through their connection to students’ cultural experiences, but their contribution to formal deduction remains limited. Keywords: geometric thinking skills, van hiele's theory, ethnomathematics.